An Analysis Study Of The Fatwa Indonesia Ulema Council (MUI) On Boycotting Israel Products With The I’tibār Al-Maalāt Theoretical Approach - Fajar Rachmadhani (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 3 Page (39-55)